Diagnostic and therapeutic dilemma due to new pattern electrocardiographic change in myocardial infarction: a case report from a remote island - Rana, Ramesh; Najme, Mohamed Shaneez; Gunaseelan,; Ara, Jubida Gulshan; Shrestha, Narottam; KC, Bijaya (Nepalese Heart Journal, 2023)
Acute myocardial infarction results due to acute disruption of coronary blood flow, commonly presented with chest pain. Electrocardiogram showing ST-segment elevation in consecutive leads is a classical ST-elevation myocardial infarction; however, atypical ST-segment elevation also can occur. We report an elderly lady who presented to the island health centre with intractable central chest pain. Electrocardiogram showed ST-segment elevation in V1 and aVR; whereas ST-depression in V4-6. With primary management, she was referred to a regional hospital. Repeat electrocardiogram showed ST-segment elevation in V1, aVR, and III; whereas ST-depression in V4-6, aVL, and I. Therefore, considering Aslanger's pattern of ECG change myocardial infarction, she was referred to the cardiac centre where coronary angiography revealed severe diffuse triple vessel disease. Primary PCI was performed on the right coronary artery initially as it is the primary culprit vessel with stenosis of other vessels. Therefore, staged angioplasty was performed on the left coronary system. Uncommon and atypical electrocardiographic presentations may be encountered in daily practice, associated with severe multiple-vessel diseases. So, it can be challenging for a cardiologist as well during interventions.